E-Government Service Through Jaket Boat Application in Thousan Islands - Cahyani Desi Puriana; Agung Edi Rustanto; Yahya Rachman Hidayat; Harits Hijrah Wicaksana (Dinasti Research, 2024)
The proliferation of electronic government (E-Government) initiatives has played a crucial role in transforming public services, particularly in enhancing effectiveness, efficiency, and accessibility. This study specifically analyses the Jaket Boat application in Thousand Island, assessing the extent to which it influences and improves public transport services. Faced with the unique geographical challenges and complex transportation needs, Thousand Island provides an ideal context for examining the application of technology in meeting and exceeding public service expectations. The Jaket Boat application, as an E-Government initiative, has been examined to assess its contribution to facilitating easier access, speeding up service processes, and enhancing the overall efficiency of the public transport system. The findings of this research are vital in informing further development of E-Government systems aimed at creating more integrated and accessible transportation services for all segments of society in Thousand Island.